Functional midterm outcome in 131 consecutive cases of surgical clubfoot treatment - Schlegel, Ulf J.; Batal, Anne; Pritsch, Maria; Sobottke, Rolf; Roellinghoff, Marc; Eysel, Peer; Michael, Joern W. (Archives of orthopaedic and trauma surgery, 2010)
Since introduction and widespread use of the Ponseti method in the last decade, the need for surgical treatment of clubfeet is nowadays limited to resistant cases. In the time before, surgery via dorsomedial release was a very common treatment option.
Online veröffentlicht am 4. August 2009
Gesehen am 13.06.2023